Analisis konsentrasi ion kalsium terhadap Bone Graft - Octarina; Nissan Ng, Kelly; Nauli Komala, Olivia (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Bone grafting is a surgical procedure that involves the transfer of bone cells from a donor to a recipient to replace bone that has been damaged by using material that can help bone regenerate. The material must be able to act as a scaffold for bone regeneration such as bone graft. The bone graft will be analyzed using Atomic Absorption Spectroscopy (AAS) due to its sensitivity and accuracy in quantifying ions at low concentrations, making an ideal technique to analyze the solubility of these biomaterials under physiological conditions. The purpose of this article is to provide information about the calcium ion concentration of bone graft material that can act as a scaffold in stimulating the healing process of bone and bone defects.